2015
DOI: 10.1615/critrevoncog.2015013566
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Treatment of Rhabdoid Tumor

Abstract: Rhabdoid tumor is a rare, highly aggressive malignancy that primarily affects infants and young children. These tumors typically arise in the brain and kidney, although extrarenal, non–central nervous system tumors in almost all soft-tissue sites have been described. SMARCB1 is a member of the SWI/SNF chromatin-remodeling complex and functions as a tumor suppressor in the vast majority of rhabdoid tumors. Patients with germline mutations or deletions affecting SMARCB1 are predisposed to the development of rhab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 119 publications
4
84
0
Order By: Relevance
“…Therefore, BCOR ITD-positive tumors and MRT are more similar in that, among each tumor group, CNS tumors exhibit unique histological features. From a genetic standpoint, soft tissue MRT have a higher incidence of homozygous deletion of the INI gene than AT/RT and renal MRT, and the mutation hotspots in the gene are exons 5 and 9 in AT/RT, whereas mutations in exon 2 are common in renal MRT (4,9). As for BCOR ITD-positive tumors, although the minimally duplicated region (p.D1725 to p.L1737) were common, the altered amino acid sequence pattern found in cases 2-4, combined with previous studies, has been observed in 4 of 25 (16%) CNS HGNET-BCOR, which has not been seen so far in CCSK or URCS/PMMTI, and duplicated regions extending toward the Nend from p.Asp1712 were more common in CNS HGNET-BCOR ( Figure 5, Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, BCOR ITD-positive tumors and MRT are more similar in that, among each tumor group, CNS tumors exhibit unique histological features. From a genetic standpoint, soft tissue MRT have a higher incidence of homozygous deletion of the INI gene than AT/RT and renal MRT, and the mutation hotspots in the gene are exons 5 and 9 in AT/RT, whereas mutations in exon 2 are common in renal MRT (4,9). As for BCOR ITD-positive tumors, although the minimally duplicated region (p.D1725 to p.L1737) were common, the altered amino acid sequence pattern found in cases 2-4, combined with previous studies, has been observed in 4 of 25 (16%) CNS HGNET-BCOR, which has not been seen so far in CCSK or URCS/PMMTI, and duplicated regions extending toward the Nend from p.Asp1712 were more common in CNS HGNET-BCOR ( Figure 5, Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to eliminate the term INI1-negative hepatoblastoma from the current classification scheme, and classify INI1-negative tumors as MRT, particularly since high-risk HB-chemotherapy regimens are not effective for treating MRT.Cancers 2019, 11, 1992 2 of 13 and radiation, and with high mortality [7][8][9]. MRT of the liver are uncommon, comprising less than 5% of malignant liver tumors in infants [7,10,11].Historically MRT was morphologically identified as a unique tumor type based on its characteristic "rhabdoid" cytologic features with abundant eosinophilic cytoplasm and eccentric nuclei [6]. In the era of molecular genomics, regardless of their anatomical site, the majority of MRT show loss of the protein product of the SMARCB1 gene, also known as BAF47/INI1/hSNF5 [12,13].…”
mentioning
confidence: 99%
“…The SWI/SNF complex controls gene transcription [18] and has a tumor suppressing function [19]. Studies have shown that biallelic inactivation of SMARCB1 seem to be both necessary and sufficient to cause cancer [11,16,20]. All rhabdoid tumors with homozygous mutations and/or deletions of SMARCB1 show loss of nuclear expression of INI1/BAF47 protein, that can be detected by immunohistochemistry [21,22].In the current classification of pediatric liver tumors, INI1-negative immunostaining in the absence of rhabdoid morphology is insufficient to diagnose MRT of the liver.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions have been demonstrated between SMARCB1/INI1 and key proteins in various pathways related to tumor proliferation and progression: the p16/RB pathway, WNT signaling3 pathway, sonic hedgehog signaling pathway and Polycomb pathway [20]. The molecular changes in AT/ RTs include a mutation in one allele with a second allele loss due to monosomy 22, deletion of 22q11.2, or an acquired copy number neutral loss heterozygosity [21,22]. Sellar AT/RTs also have a higher prevalence of biallelic INI1 alterations compared to AT/RTs in other locations [9].…”
Section: Discussionmentioning
confidence: 99%